Profil Pemahaman Konsep Siswa SMA dalam Menyelesaikan Masalah Program Linear Berdasarkan Perbedaan Gender - Yeny Kurmayningsih; Didik Hermanto; Mety Liesdiani (Universitas PGRI Madiun, 2020)
This research is a qualitative descriptive study conducted in class XI. The research subjects consisted of one masculine male student and one feminine female student. The research instrument used a Gender Test, Interview Guidelines and Problem Solving Tasks (TPM). The data collection technique used in this research was the problem solving task-based interview technique. The technique of testing the validity of the data used time triangulation. The data analysis technique used was reduction, presentation, and conclusion. Based on the data analysis that has been done, the following conclusions are obtained. The profile of understanding the concept of masculine male students in solving linear programming problems includes: writing what is known and what is asked which is emphasized by the presence of a question mark